2008
DOI: 10.1099/vir.0.83686-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against Epstein–Barr virus gp78 antigen: a novel marker for serological diagnosis of nasopharyngeal carcinoma detected by xMAP technology

Abstract: Immunoglobulin (Ig) A and/or IgG reactivities to several Epstein-Barr virus (EBV) antigens have been used to facilitate diagnosis of nasopharyngeal carcinoma (NPC). However, antibodies against gp78, an EBV membrane glycoprotein, have not been examined to this day. In this study, we utilized Luminex multi-analyte profiling (xMAP) technology to analyse antibody responses to a synthetic peptide of gp78 in sera samples from 95 NPC patients and 91 healthy controls. Our results showed the sensitivity and specificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 48 publications
1
20
0
2
Order By: Relevance
“…Serological studies on Burkitts's lymphoma and NPC have shown that elevated antibody titers against EBV lytic antigens may correlate with advanced cancer stages, poor prognoses, or poor tumor therapy. 6,9,41,42 Some clues have indirectly indicated that EBV reactivation into lytic cycle may occur during tumor development. 43,44 In our study, matured and budding virions were observed, directly confirming that EBV reactivation occurred spontaneously from latent genome to viral production in some cells at the site of tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…Serological studies on Burkitts's lymphoma and NPC have shown that elevated antibody titers against EBV lytic antigens may correlate with advanced cancer stages, poor prognoses, or poor tumor therapy. 6,9,41,42 Some clues have indirectly indicated that EBV reactivation into lytic cycle may occur during tumor development. 43,44 In our study, matured and budding virions were observed, directly confirming that EBV reactivation occurred spontaneously from latent genome to viral production in some cells at the site of tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…The recent development of spectrally-distinguishable fluorescent beads (Luminex) (Kellar and Iannone, 2002) has resulted in the widespread use of antigen-coupled beads for monitoring antibodies in sera by flow cytometry. These bead arrays have been adapted for serologic screening of antigens and has been described for up to ten antigens for HIV (Opalka et al, 2004), HPV (Opalka et al, 2003; Dias et al, 2005), Epstein-Barr virus (Klutts et al, 2004; Binnicker et al, 2008; Gu et al, 2008), B. anthracis (Biagini et al, 2004; Biagini et al, 2005), Influenza (Drummond et al, 2008) and M. tuberculosis (Khan et al, 2008). When using purified antigens covalently linked on the beads, multiplexed serologic screening is both highly sensitive and efficient, but requires bacterial protein production and protein purification.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, increasing availability of these assays with distinct antigenic specifi city makes it possible to use the assays in combination in an approach to effect diagnosis of NPC based on EBV antibody spectrum rather than the level of individual antibodies. Reports by Gu et al showed that IgA and IgG antibodies against gp78, a membrane protein, were statistically higher in NPC populations than in healthy controls (49). They suggested the use of Luminex multi-analyte profi ling (xMAP) technology to detect multiple parameters in NPC, such as antibodies against gp78, VCA, EA-D and EBNA1 simultaneously (see Table 1).…”
Section: Markers For Diagnosis Of Npcmentioning
confidence: 99%